Acute Ischemic Lesions Associated with Impairments in Expression and Recognition of Affective Prosody - Amy Elizabeth Wright (Frontiers in Psychology, 2015)
The ability to convey emotion through variations in tone of voice (affective prosody) is crucial for normal social interaction. Our goals were to: (1) test the hypothesis that there are double dissociations in impairment of expression and recognition of affective prosody after acute right hemisphere ischemic stroke; and (2) to identify areas of acute ischemia associated with impaired expression and/or recognition of affective prosody after acute ischemic right hemisphere stroke.